An overview of intuitionistic linguistic fuzzy information aggregations and applications - Peide Liu; Hui Gao (Marine Economics and Management (MAEM), 2018)
Purpose - Intuitionistic linguistic fuzzy information (ILFI), characterized by linguistic terms and intuitionistic fuzzy sets (IFSs), can easily express the fuzzy information in the process of muticriteria decision making (MCDM) and muticriteria group decision making (MCGDM) problems. The purpose of this paper is to provide an overview of aggregation operators (AOs) and applications of ILFI. Design/methodology/approach - First, some meaningful AOs for ILFI are summarized, and some extended MCDM approaches for intuitionistic uncertain linguistic variables (IULVs), such as extended TOPSIS, extended TODIM, extended VIKOR, are discussed. Then, the authors summarize and analyze the applications about the AOs of IULVs. Findings - IULVs, characterized by linguistic terms and IFSs, can more detailed and comprehensively express the criteria values in the process of MCDM and MCGDM. Therefore, lots of researchers pay more and more attention to the MCDM or MCGDM methods with IULVs. Originality/value - The authors summarize and analyze the applications about the AOs of IULVs Finally, the authors point out some possible directions for future research.
Keywords: 330; Applications; Intuitionistic linguistic fuzzy information; Intuitionistic uncertain linguistic variables; Aggregation operators